Meeting the New AACP Competencies in Genetics and Clinical Pharmacogenomics at the University of Minnesota - Jacob Brown; Lindsay A Sorge; William S Oetting; Pamala A Jacobson; Chrystian Pereira (INNOVATIONS in Pharmacy, 2024)
Objective: Pharmacogenomics (PGx) is increasingly being used for creating individualized treatments for patient care. Healthcare professionals, especially pharmacists, need to understand how genetic variation impacts the efficacy and toxicity of medications. Due to the breadth and complexity of PGx-related information, it has been challenging to determine what information should be included in pharmacy curricula and how best to educate students.